The status of civil servants - between aspirations towards professional excellence and political interference - Anamaria Groza (Juridical Tribune, 2018)
The Romanian society has, as a national objective, a public administration outside the political influence and the recruitment of competent and performant public servants. One of the instruments to realize this objective is, no doubt, the legal status of the public servants. This study is aimed to identify and analyse the elements of vulnerability witch the Law 188/1999 concerning the public servants and the project of the Administrative Code contain, from the perspective of the political influences. The main issue of the study is to be aware of the institutions, procedures and factors witch make fragile the legal status of the public servants, allowing, by example, the political parties membership of the public servants or their recruitment in absence of a national competition, organised by an entity specialised in the development of the public function in Romania. The project of the Administrative Code brings remedies only in part for the existing problems, while amplifies others. O very difficult, actual and vulnerable matter is the policy of salaries of public servants, in the context of the Decision n. 794/2016 of the Constitutional Court. The research has an explicative, but also a critic character. Also, solutions are offered in order to increase the degree of accomplishment of a competent, transparent and political neutral administration.